(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the influence of interactive and intellectual methods on students’ motivation and their significance in the educational process. The intellectual method is justified as an approach that activates students’ cognitive activity and develops independent thinking, analytical skills, and problem-solving abilities. Based on the experiences of developed countries, project- and presentation-based learning increases students’ knowledge level, self-confidence, and the ability to express ideas freely. Moreover, using the intellectual method in teaching English is an effective tool for enhancing students’ reading, speaking, and writing skills. Research results indicate that this method strengthens students’ intrinsic motivation and supports conscious, long-term knowledge acquisition.